PECULIARITIES OF THE STRUCTURAL ORGANIZATION OF THE GEMOMICROCIRCULATOR GENTLE OF THE GENTAL MUSCLE RATS - A. O. Hrad (Vіsnik Naukovih Doslіdžen', 2017)
The chewing muscle constantly and intensively works, therefore it has a dense vascularization, and its blood supply concerns to a regional blood flow. As known in various pathological conditions and diseases, the actual blood flow disturbance in the hemocirculatory channel (HM CR) leads to the development of various genesis myopathies.